2016
DOI: 10.1038/ncomms11025
|View full text |Cite
|
Sign up to set email alerts
|

Sequence features accurately predict genome-wide MeCP2 binding in vivo

Abstract: Methyl-CpG binding protein 2 (MeCP2) is critical for proper brain development and expressed at near-histone levels in neurons, but the mechanism of its genomic localization remains poorly understood. Using high-resolution MeCP2-binding data, we show that DNA sequence features alone can predict binding with 88% accuracy. Integrating MeCP2 binding and DNA methylation in a probabilistic graphical model, we demonstrate that previously reported genome-wide association with methylation is in part due to MeCP2's affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 52 publications
5
53
1
Order By: Relevance
“…However, whether the selective binding of MECP2 to mCA sequences in different neuronal subtypes accounts for neuronal subtype-specific gene mis-regulation in RTT is not known. In mixed neuronal populations MECP2 has been shown to bind ubiquitously across the genome accumulating at near histone-octamer levels (Skene et al, 2010), and studies have suggested that MECP2 might bind to DNA to some extent regardless of the DNA methylation status (Baubec et al, 2013; Rube et al, 2016). Because accumulating evidence indicates that MECP2 binds avidly to mCA sequences in neurons to recruit the transcriptional co-repressor NCOR and thereby temper gene transcription, we asked whether MECP2 might function to enforce the neuronal subtype-specific dampening of the transcription of mCA-marked genes.…”
Section: Resultsmentioning
confidence: 99%
“…However, whether the selective binding of MECP2 to mCA sequences in different neuronal subtypes accounts for neuronal subtype-specific gene mis-regulation in RTT is not known. In mixed neuronal populations MECP2 has been shown to bind ubiquitously across the genome accumulating at near histone-octamer levels (Skene et al, 2010), and studies have suggested that MECP2 might bind to DNA to some extent regardless of the DNA methylation status (Baubec et al, 2013; Rube et al, 2016). Because accumulating evidence indicates that MECP2 binds avidly to mCA sequences in neurons to recruit the transcriptional co-repressor NCOR and thereby temper gene transcription, we asked whether MECP2 might function to enforce the neuronal subtype-specific dampening of the transcription of mCA-marked genes.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, these comparative data strongly suggest that the combination of analyzing both loss-of-function Mecp2 rodent models may provide a significant advantage for identifying transcriptional changes and likely other biochemical and molecular changes that occur in the human RTT brain that may not have been predicted in analyses of either rodent model alone. In the context of recent findings suggesting that MeCP2 may regulate the expression of long genes in a cell-type and brain-region specific manner (90,91), and preferentially bind to DNA at methylated cytosine at CG sites (92) yet also bind to methylated cytosine at non-CG sites (69) as well as nucleosomal sequences with high GC content alone (93), it would be highly informative to pursue similar studies using the Mecp2 rat model to further clarify the role of MeCP2 in the epigenetic regulation of gene expression and its impact on disease features of RTT and related disorders.…”
Section: Discussionmentioning
confidence: 96%
“…Contrasting with this conclusion, a recent study using olfactory bulb neurons, reported that MeCP2 is enriched at non-methylated CGIs and that DNA methylation is a minor determinant of binding [20]. This conflicts with the findings of our study and several previously published MeCP2 ChIP experiments, all of which found a dramatic drop in MeCP2 binding at CGIs in cultured cells [15], whole mouse brain [16], hypothalamus [27], cortex and cerebellum [26] coupled with DNA methylation-dependent occupancy of the genome.…”
Section: Discussionmentioning
confidence: 98%